x-6(8x+6)=5-47x

Simple and best practice solution for x-6(8x+6)=5-47x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x-6(8x+6)=5-47x equation:


Simplifying
x + -6(8x + 6) = 5 + -47x

Reorder the terms:
x + -6(6 + 8x) = 5 + -47x
x + (6 * -6 + 8x * -6) = 5 + -47x
x + (-36 + -48x) = 5 + -47x

Reorder the terms:
-36 + x + -48x = 5 + -47x

Combine like terms: x + -48x = -47x
-36 + -47x = 5 + -47x

Add '47x' to each side of the equation.
-36 + -47x + 47x = 5 + -47x + 47x

Combine like terms: -47x + 47x = 0
-36 + 0 = 5 + -47x + 47x
-36 = 5 + -47x + 47x

Combine like terms: -47x + 47x = 0
-36 = 5 + 0
-36 = 5

Solving
-36 = 5

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 4X+6=7-3 | | -2/3*4=x | | 7p-5(p-q)-p= | | -2/3*4= | | log(8x+11)=2 | | 2x+3=3x+20 | | 7x+2(x-5)=4 | | 5X+6+4X=3-6 | | 10(x+2)-4(2x+1)=2(x+6) | | E^9x=5.9 | | F(x)=-x^2+8x+7 | | 9n+2n-5=-60 | | 8(a+2)=72 | | F(x)=-x^2-6x+5 | | 3x-4+5x+20=180 | | 3x-4+5x+20=360 | | 5=log(x+1) | | 8+5(x-7)=8-4(x-8) | | 5X-7X+X=4-2X | | 5e+2.5=2.5-7.5c | | -5.5+3.5(1-9.5k)=25.5 | | 0.24x+3.8x=-2.02 | | 8+5x-35x=8-4x-32 | | 4(2b-3x)=7b+5x | | 8+5x-35x=8-4x+32 | | 8x-17b=7x | | n=2/4*7/8 | | 7+3x=-5x+13 | | 12x-(x+3)=30 | | 4(2x-3b)=7x+5b | | 12x-(x+3)=4 | | 2x-3+4x+1=0 |

Equations solver categories